Simulation and prediction of residential grid-connected photovoltaic system performance - Siti Nor Nadhirah Ibrahim; Hedzlin Zainuddin; Yang Ilya Akila Abdul Rahim; Nur Awliyah Mansor; Nurmalessa Muhammad; Farah Liyana Muhammad Khir (Institute of Advanced Engineering and Science, 2023)
This paper presents the analysis of the actual, predicted, and simulated technical performance of a residential 2.835 kWp retrofitted grid-connected photovoltaic (GCPV) system under the feed-in-tariff (FiT) scheme in Klang, Malaysia located in the equatorial region. The technical performance indices of the GCPV system were assessed based on the three-year energy production in 2018, 2019 and 2020. The actual and predicted technical performance were calculated using SEDA mathematical model, which the solar irradiation data was acquired from PVsyst software. Meanwhile, the simulated technical performance was obtained using PVsyst software. The results showed that the prediction using mathematical model has higher percentage difference within the range of 12.54-13.29%, compared to PVsyst simulation that was within 7.93-11.93%. This study has highlighted the factors that contributed to the technical performance underprediction of both mathematical model and PVsyst simulation, which are the estimation of losses and annual irradiation data accuracy. Lastly, the FiT gross income calculated for the three consecutive years were within the range of 3310.80 MYR and 3357.30 MYR. This FiT gross income result conveys an example of Malaysian case study, to enlighten the public, on the economic aspect of installing GCPV system under FiT scheme.